Perception - Akins, Kathleen (Vancouver studies in cognitive science, 1996)
1. Introduction, Kathleen A. Akins. 2. Explaining Why Things Look the Way They Do, Kirk Ludwig. 3. A Feedforward Network for Fast Stereo Vision, Paul M. Churchland. 4. On the Failure to Detect Changes in Scenes Across Seccades, John Grimes. 5. On the Function of Visual Representation, Dana Ballard. 6. Filling In: Why Dennett is Wrong, P.S. Churchland and V.S. Ramachandran. 7. Seeing is Believing--Or Is It?, Daniel C. Dennett. 8. Ships in the Night: Churchland and Ramachandran on Dennett's Theory of Consciousness, Kathleen A. Akins and Steven Winger. 9. Lewis on What Distinguishes Perception fro.